A Study of How the Political System of India is Beneficial or Harmful for Democracy - Chaudhary, Pramod Kumar (Integrated Journal for Research in Arts and Humanities, 2023)
A type of governance known as democracy is one in which members of the population take part in the making of decisions either directly or indirectly via the use of a system of representation that includes the holding of free elections on a regular basis. It is generally agreed that India's democracy is the biggest one in existence on a global scale. In a democracy, the citizens or their representatives have the power, as well as the people are the ultimate authority in every aspect of administration. This holds true regardless of the kind of government in place. On the other hand, democracy has been met with several obstacles in contemporary India, such as social and economic disparities, unemployment and poverty casteism, illiteracy, corruption, communalism, terrorism, and population expansion. It is essential that this issue be resolved if India is to continue to function as a genuine parliamentary democracy. In this article, an attempt is made to investigate and analyse the democratic system that is now in the country and what the impact of the Indian political system is on democracy. In addition to this, it proposes a number of feasible actions or adjustments to existing institutions that may be made in order to make India's democracy more robust and long-lasting.